Omics technologies : tools for food science - Benkeblia, Noureddine (Boca Raton, FL : CRC Press, 2012)
'Examining the application of genomic information and high-throughput profiling technologies as tools for the nutrition and food science industries, this book takes a particular interest in the transformation from industrial to sustained food technologies and the role of these omics tools to mitigate the growing pressure of limited natural resources and environmental degradation. Providing detailed descriptions right down to the molecular level, it discusses the prominence of diet and food components as prime environmental factors that affect the genome, transcriptome, proteome, and metabolome and how these delicate interactions define individual health or disease'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Food -- Biotechnology; Sustainability